A New EOR Technology: Gas Alternating Gas Injection - Samba, Mohammed Alsharif; Aldokali, Ibrahim; Elsharaf, Mahmoud Omran (Pekanbaru Riau: Program Studi Teknik Perminyakan FT Universitas Islam Riau, 2019)
A new method of enhanced oil recovery has been developed and applied to a simulation using some of data from the fifth SPE paper